2015
DOI: 10.1162/jocn_a_00819
|View full text |Cite
|
Sign up to set email alerts
|

Stable Task Representations under Attentional Load Revealed with Multivariate Pattern Analysis of Human Brain Activity

Abstract: Performing multiple tasks concurrently places a load on limited attentional resources and results in disrupted task performance. Although human neuroimaging studies have investigated the neural correlates of attentional load, how attentional load affects task processing is poorly understood. Here, task-related neural activity was investigated using fMRI with conventional univariate analysis and multivariate pattern analysis (MVPA) while participants performed blocks of prosaccades and antisaccades, either with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
(111 reference statements)
2
1
0
Order By: Relevance
“…5d; see also (Todd et al 2005;Shulman et al 2007;Asplund et al 2010), nevertheless discriminated the switching rule from the hold rules; its peak classification performance was better than chance, t(13) = 2.26, P < 0.05. This decoding result may fit well with the proposition that the TPJ is involved in evaluating/analyzing the meaning of behaviorally relevant stimuli (Doricchi et al 2010;Geng and Mangun 2011;Chan et al 2015;Vossel et al 2015). Along this vein, a recent study (Lee and McCarthy 2016) demonstrated that the activation pattern in the TPJ correlated across tasks with cognitive demands as varied as biological motion, theory of mind, and attention reorienting.…”
Section: Multivariate Resultssupporting
confidence: 78%
“…5d; see also (Todd et al 2005;Shulman et al 2007;Asplund et al 2010), nevertheless discriminated the switching rule from the hold rules; its peak classification performance was better than chance, t(13) = 2.26, P < 0.05. This decoding result may fit well with the proposition that the TPJ is involved in evaluating/analyzing the meaning of behaviorally relevant stimuli (Doricchi et al 2010;Geng and Mangun 2011;Chan et al 2015;Vossel et al 2015). Along this vein, a recent study (Lee and McCarthy 2016) demonstrated that the activation pattern in the TPJ correlated across tasks with cognitive demands as varied as biological motion, theory of mind, and attention reorienting.…”
Section: Multivariate Resultssupporting
confidence: 78%
“…A similar result was observed in the DLPFC, where the classifier decoded the two types of saccades 64.25% of the time. Our findings are at least partially consistent with Chan et al (2015) [ 39 ] who showed that the SVM predicted the saccade type in several cortical regions, among these the FEF and IPS. However, the highest accuracy observed by Chan and colleagues was 57.3% in the FEF and 58.8% in the IPS.…”
Section: Discussion: Cortical Activitysupporting
confidence: 93%
“…This might enable fast transfer of abstract rules (Cole et al, 2011) and stable selective attention towards task-relevant information (Zhang et al, 2013). Stable task representations have also been observed under varying attentional loads (Chan, Kucyi, & DeSouza, 2015), further highlighting the context-independent coding of tasks. Thus, our findings of such invariant neural representations do not rule out a dynamic adjustment of task specific neurons, as the adaptive coding hypothesis (Duncan, 2001(Duncan, , 2010Waskom et al, 2014) suggests.…”
Section: Influence Of Switching On Task Representation In Fronto-parimentioning
confidence: 85%